“IMPLEMENTACIÓN DEL DERECHO DE TRANSFORMACIÓN EN EL RÉGIMEN DE LA PROPIEDAD INTELECTUAL AMPARADO POR LA DOCTRINA DEL USO JUSTO PARA LA EXPLOTACIÓN DE OBRAS DERIVADAS”. - Román Medina, Jenniffer Daniela (2021)
This degree thesis is entitled: "Implementation of the law of transformation in the intellectual property regime protected by the doctrine of fair use for the exploitation of derivative works", the need for its execution arises due to the analysis carried out to the Organic Code of the Social Economy of Knowledge, Creativity and Innovation, which frames the figure of fair use. It is incorporated in the second paragraph of limitations and exceptions of copyright, of the aforementioned legal body. The origin of “uso justo” comes from an Anglo- Saxon trend, called “fair use”, which allows the reuse of copyrighted material without the permission of the original owner. The partial implementation of fair use in Ecuadorian legislation generates problems, by extrapolating a figure from an Anglo-Saxon current to a continental current, which denatures the original essence of fair use. The fair use doctrine is applied more frequently in the administrative channels of social networks, on platforms such as YouTube, Facebook, Twitch that violate constitutional guarantees such as the right to due process. For this reason, it is necessary to implement solid regulations in the judicial system to ensure compliance with basic constitutional guarantees, which are frequently unobserved in digital media. The absence of a complementary regulation to the figure of fair use prevents a correct application of this figure in a practical context. In the same way the lack of a doctrinal and jurisprudential analysis prevents the application of fair use, since there 5 are no criteria on which Ecuadorian judges can rely, to determine whether a content or work is protected by fair use. Which makes it impossible for them to issue reasoned judicial decisions. In the development of the thesis, materials and methods were applied to elaborate the present investigation, likewise interviews and surveys were carried out with prominent professionals of the Law, as well as with consolidated digital content generators, results that served to propose a legal reform project to ensure that content creators' basic constitutional rights are respected. Therefore, the incorporation of the right of transformation, as an unnumbered article in the Organic Code of the Social Economy of Knowledge, Creativity and Innovation, in the Second Paragraph of limitations and exceptions of the author, as well as the substitution of numeral 2 of article 211 ibid, the substitution of numeral 1 of article 212 ibid, and finally the substitution of article 105 ibid, will guarantee that the figure of fair use is properly applied in the judicial process, respecting the essence of the figure, which will determine the guidelines so Judges can strengthen their criteria when issuing reasoned judicial decisions, and simultaneously respect the rights to due process, freedom of expression and even the right to education, of digital creators and consumers as the case may be.